Ets-1 p27: a novel Ets-1 isoform with dominant-negative effects on the transcriptional properties and the subcellular localization of Ets-1 p51. - Laitem, C; Leprivier, G; Choul-Li, S; Begue, A; Monte, D; Larsimont, D; Dumont, P; Duterque-Coquillaud, M; Aumercier, M (2009)
The transcription factor Ets-1 is implicated in various physiological processes and invasive pathologies. We identified a novel variant of ets-1, ets-1Delta(III-VI), resulting from the alternative splicing of exons III to VI. This variant encodes a 27 kDa isoform, named Ets-1 p27. Ets-1 p27 lacks the threonine-38 residue, the Pointed domain and the transactivation domain, all of which are required for the transactivation of Ets-1 target genes. Both inhibitory domains surrounding the DNA-binding domain are conserved, suggesting that Ets-1 p27, like the full-length Ets-1 p51 isoform, is autoinhibited for DNA binding. We showed that Ets-1 p27 binds DNA in the same way as Ets-1 p51 does and that it acts both at a transcriptional and a subcellular localization level, thereby constituting a dual-acting dominant negative of Ets-1 p51. Ets-1 p27 blocks Ets-1 p51-mediated transactivation of target genes and induces the translocation of Ets-1 p51 from the nucleus to the cytoplasm. Furthermore, Ets-1 p27 overexpression represses the tumor properties of MDA-MB-231 mammary carcinoma cells in correlation with the known implication of Ets-1 in various cellular mechanisms. Thus the dual-acting dominant-negative function of Ets-1 p27 gives to the Ets-1 p27/Ets-1 p51 ratio a determining effect on cell fate.